2021
DOI: 10.1039/d1ra06717f
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of formaldehyde emission from urea-formaldehyde resin with a small quantity of graphene oxide

Abstract: This is the first experiment to demonstrate that GO effectively prevents formaldehyde emission from UF resin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…29 GnO is typically derived from graphite oxidation using the Hummers' technique. 30,31 It possesses a folded structure and exhibits a significantly high specific surface area when compared with other carbonbased materials. Being a two-dimensional carbon nanomaterial, GnO serves as a valuable precursor for the cost-effective and large-scale manufacturing of graphene-based materials.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…29 GnO is typically derived from graphite oxidation using the Hummers' technique. 30,31 It possesses a folded structure and exhibits a significantly high specific surface area when compared with other carbonbased materials. Being a two-dimensional carbon nanomaterial, GnO serves as a valuable precursor for the cost-effective and large-scale manufacturing of graphene-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 Recently, Saito et al demonstrated through experimental and theoretical approaches that GnO in urea formaldehyde (UF) adhesive is a superb formaldehyde scavenger leading to a very low emission into the environment. 30 The objective behind this study is to investigate the impact of GnO, prepared through the Hummers method from graphite particles, on the development of ecofriendly plywood panels containing PF resins with reduced volatile organic compounds (VOC) emissions. This research aims to explore the potential of GnO in reinforcing PF adhesives for improved plywood performances and to study its role in scavenging the free formaldehyde emitted to the environment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations